VD_FINDINFO HC / 2014 / 274 vom 18. März 2014 - VD Tribunal cantonal (2014)
SERVITUDE, DROIT DE PASSAGE, DROIT DE PASSAGE NÉCESSAIRE, ÉTENDUEEN GÉNÉRAL, PLACE DE PARC | 694 CC, 737 CC, 738 CC, 739 CC, 741 CC